A new meroterpenoid from endophytic fungus Talaromyces amestolkiae CS-O-1. (December 2020) - Fu, Yunmei; Li, Chunhe; Zhu, Jing; Zhang, Luting; Wang, Yu; Chen, Qili; Xu, Liang; Zhang, Songya; Fang, Yue; Liu, Tao
Abstract: Talaromyces amestolkiae CS-O-1, isolated from Tripterygium Wilfordii Hook. f., was identified based on its ITS and 18S rDNA gene sequencing. A new meroterpenoid, chrodrimanin T (1 ), along with six known compounds, nicotinamide (2 ), penipyridone D (3 ), penipyridone A (4 ), 3-benzylidene-8, 8a-dihydroxy-2-methyl-hexahydro-pyrrolo[1, 2-a]pyrazine-1, 4-dione (5 ), butyl-isobutyl-phthalate (6 ), and aspergillumarin A (7 ), were isolated from Talaromyces amestolkiae CS-O-1. The structures and relative configurations of these compounds were established by the analysis of HRMS, 1D and 2D-NMR spectroscopy and the comparison with data in the literature. The compounds 2 –6 were first isolated from Talaromyces genus. Herein, the chemotaxonomic significance of these compounds is described. Highlights: Seven compounds were isolated from the endophytic fungus Talaromyces amestolkiae CS-O-1. Compound 1 is a new meroterpenoid compound. Compounds 2 –6 were isolated for the first time in Talaromyces genus. The significance of chemotaxonomy for these compounds was discussed.